Pelaksanaan Sertifikasi Tanah Wakaf Dengan Pendekatan Fishbone Diagram Analysis (Studi Di Kecamatan Sewon Kabupaten Bantul) (UIN Sunan Kudus, 2020)
Waqf is one of rapidly developing Islamic economic instruments, but more waqf land registered still have no a legal certificate of waqf. It is as occurred in Sewon Sub-district, Bantul Regency in which of 350 locations of waqf land, 115 have no certificate. In fact, the administration for the waqf land is the main thing that must be accomplished. This then makes the waqf land has no legal force that later on can emerge the conflict of waqf land. This is a qualitative-descriptive research with field research. The data were collected by means of observation, documentation and interview that later on were analyzed using fishbone diagram analysis to figure out the root of the problem and to offer a proper solution. The results of the research showed that (1) the process of certification was hampered by finance, (2) the function of controlling was not implemented, (3) being officer of waqf is a side-job, (4) the waqf land had no certificate, and (5) the agreement process of heir. Then, the solution that can be offered is that there is a needs for proposing the fund from government to facilitate the process in making certificate for the waqf land, monitoring the process in making certificate of waqf land, the recruitment of officers only focusing on managing the waqf matter and a system that can facilitate the agreement of heir and a registration for the waqf land that has no certificate.